TRM vs FRP jacketing in shear strengthening of concrete members subjected to high temperatures - Tetta, Zoi C.; Bournas, Dionysios A. (Composites. Part B, Engineering, 2016)
This paper presents the first study on the performance of TRM and FRP jacketing in shear strengthening of reinforced concrete (RC) members subjected to ambient and high temperatures, including both medium-scale rectangular beams and full-scale T-beams. Key parameters investigated on the medium-scale rectangular RC beams include: (a) the matrix used to impregnate the fibres, namely resin or mortar, resulting in two strengthening systems (TRM or FRP), (b) the level of high temperature to which the specimens are exposed (20 °C, 100 °C, 150 °C, 250 °C), (c) the strengthening configuration (side-bonding, U-wrapping and full-wrapping), (d) the number of jacketing layers (2 and 3) and (e) the textile properties (geometry, material). The effectiveness of both non-anchored and anchored TRM jackets in shear strengthening of full-scale T-beams at high temperature was also studied. It is concluded that TRM possess excellent performance as strengthening material at high temperature. TRM jacketing remained very effective in shear strengthening of concrete at high temperature; on the contrary the effectiveness of side-bonding and U-wrapping FRP jacketing was reduced nearly to zero when subjected at temperatures above the glass transition temperature.